Maqueripe Bay, Via Chaguaramas, Trinidad - (:unkn) unknown (Ace Printery,[Trinidad and Tobago], 2011)
The postcard shows beachgoers at Maqueripe Bay, Chaguaramas, Trinidad.
Colour: Coloured; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Inlets--Trinidad and Tobago; Beaches--Trinidad and Tobago; Beachgoers--Trinidad and Tobago; Bays--Trinidad and Tobago; Bathing beaches--Trinidad and Tobago; Maqueripe Bay